POSITION AND ATTACHMENT MODEL OF EXPENDITURE COLOSTRUM AND BREAST MILK PRODUCTION USING THE TRIANGULAR OF LOVE THEORY APPROACH - Nurul Pujiastuti; Hurun Ain; Budiono Budiono (Universitas Airlangga, 2022)
Introduction: Breastfeeding is the natural process of becoming a mother. However, not all mothers can breastfeed with the correct breastfeeding technique, causing problems in breastfeeding and affecting milk production. Methods: This study analyzes the model of colostrum and breast milk production using the Triangle of love theory approach. The research design was a descriptive, explanatory survey. The sample was 95 breastfeeding mothers using the multistage random sampling technique. The sample criteria were mothers breastfeeding infants aged 0-6 months with spontaneous delivery in two public health centers in Sidoarjo regency. Data analysis using structural equation test-partial least square (PLS). Result: The results showed that there was an effect of health workers on colostrum and breast milk production (T = 1.423), there was a lifestyle effect on position and attachment (T = 1.475), and there was an effect of position and attachment on colostrum and breast milk production (T = 2.142). Conclusion: The position and attachment of breastfeeding using the Triangle of love theory approach can help increase colostrum and milk production of nursing mothers. Keywords: attachment, breastfeeding position, triangle of love